英汉“哭”类动词的语义成分及词化模式分析 - Xuemei Jiang; Chili Li (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
This study employs semantic component analysis and lexicalization theory to conduct a comparative analysis of the semantic components and lexicalization patterns of “cry” type verbs in English and Chinese. The findings reveal that these verbs in both languages exhibit both universality and specificity in their semantic components and lexicalization patterns. The core semantic components determine the semantic field of synonymous verbs, while peripheral components differentiate their nuances. Furthermore, “cry” type verbs in both languages follow the lexicalization pattern of “action + manner + cause + X”. This study advances the semantic and lexicalization analysis of “cry” type verbs in English and Chinese, offering novel theoretical and translational insights. Through systematic examination of their semantic components and lexicalization patterns, it enables more precise cross-linguistic understanding and application in translation practice.